2010
DOI: 10.1097/iae.0b013e3181d95261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes Between 23-Gauge and 20-Gauge Vitrectomy in Patients With Proliferative Diabetic Retinopathy

Abstract: Twenty three-gauge transconjunctival sutureless vitrectomy appears to be as effective for proliferative diabetic retinopathy as 20-gauge vitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 28 publications
2
35
2
Order By: Relevance
“…Transient hypotony of 23g has been noted in several other studies. Park et al [21] found 0% (66/101) of their 20g and 22% (45/101) of their 23g group to be under <8 mm Hg at day 1 postoperatively. Both Akçay et al [22] and Lott et al [23] similarly found high rates of transient hypotony in their 23g groups; 9.8% (34/350) and 10% (10/100) of the eyes treated with 23g had an IOP of <6 mm Hg 1 day postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Transient hypotony of 23g has been noted in several other studies. Park et al [21] found 0% (66/101) of their 20g and 22% (45/101) of their 23g group to be under <8 mm Hg at day 1 postoperatively. Both Akçay et al [22] and Lott et al [23] similarly found high rates of transient hypotony in their 23g groups; 9.8% (34/350) and 10% (10/100) of the eyes treated with 23g had an IOP of <6 mm Hg 1 day postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…About ten years ago trans conjunctival sutureless 23 gauge vitrectomy started to replace conventional 20 gauge technique and offers comparable safety and efficacy as well as reduced surgerytimes and faster rehabilitation of patients [69] .…”
Section: Proliferative Diabetic Retinopathymentioning
confidence: 99%
“…[888990] Park et al . [91] reported comparable rates of postoperative bleed following 23 gauge (17%) versus 20-gauge (26%) vitrectomy. [91] Khuthaila et al .…”
Section: Role Of Preoperative Intravitreal Bevacizumabmentioning
confidence: 99%